A hole modification layer and perovskite solar cell and preparation method thereof
Patent Information
- Application Number
- CN202510491363.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2026-10-30
AI Technical Summary
尽管这些材料可以一定程度上覆盖界面缺陷,然后像无机材料,其功能性单一,仅能调控钙钛矿和金属氧化物界面能级,作为一个场钝化层
[0011]与现有技术相比,本发明的空穴修饰层的制备材料为N1、N2、N3、N4中任意一种,该材料不仅可在氧化镍表面可以形成界面偶极,改变氧化镍表面的能带排布,此外,N1、N2、N3或N4材料分子结构中的氧原子和硒原子上的孤对电子可以与钙钛矿层中的铅离子形成键合作用,钝化钙钛矿埋底离子缺陷。这些材料的引入可有效提高钙钛矿太阳电池的性能。其中将N1、N2、N3或N4材料引入到钙钛矿太阳能电池中,可以提升最终的光电转换效率。N1、N2、N3或N4材料不仅可以有效钝化氧化镍的表面缺陷,抑制氧化镍对钙钛矿的降解,提升了界面处载流子的提取率,减少载流子的复合,同时分子结构中的氧原子可以有效地钝化钙钛矿埋底界面的离子缺陷。将N1、N2、N3或N4材料应用到p-i-n钙钛矿体系中,制备的钙钛矿太阳能电池的开路电压可从1.10V提升至1.18V,电流密度可从24.42mA/cm2提升至25.23mA/cm2,光电转换效率由22.26%提高至24.73%。
Smart Images

Figure CN123021886A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of perovskite solar cell technology, and specifically relates to a hole modification layer, a perovskite solar cell, and a method for preparing the same. Background Technology
[0002] In perovskite solar cells, energy level matching and charge transfer efficiency at the interface play a decisive role in device performance. The perovskite active layer and electrodes are typically coupled through an electron transport layer (ETL) and a hole transport layer (HTL). However, numerous defects and chemical instabilities at the interface of polycrystalline perovskite films lead to severe interfacial charge recombination and energy loss, reducing the photoelectric conversion efficiency of perovskite solar cells. Furthermore, the presence of interface defects accelerates the degradation of perovskite materials, decreasing the long-term operational stability of perovskite solar cells. Therefore, interface engineering has become an important means to improve the performance of perovskite solar cells.
[0003] Existing small organic molecules have been widely used in interface modification due to their tunable structure, ease of functionalization, and simple preparation. In particular, small organic molecules can effectively passivate buried interface defects in perovskite solar cells through a combination of chemical bonding and physical adsorption, thereby improving the performance and stability of perovskite solar cells. Although current small organic molecule interface materials can effectively passivate buried interface defects, regulate the band structure at the perovskite-metal oxide interface, and promote efficient charge transport at the buried interface, the polycrystalline nature of perovskite materials and the presence of numerous ion vacancies (such as Pb) within them remain significant challenges. 2+ I - Defects, whether on the perovskite lower surface or the metal oxide upper surface, can significantly reduce carrier lifetime and migration efficiency. Therefore, these defects can cause severe nonradiative recombination losses, impairing device performance. To overcome these problems, researchers have developed various passivation materials and strategies, such as inorganic passivation materials like alumina and lithium fluoride, or polymeric materials like polymethyl methacrylate (PMMA) or polystyrene (PS), or small molecules with phosphate groups. While these materials can cover interface defects to some extent, like inorganic materials, their functionality is limited, only able to modulate the energy levels at the perovskite-metal oxide interface, acting as a field passivation layer. Polymer materials are more sensitive to thickness, and small molecule passivators currently have relatively simple structures with few functional sites for defect passivation. Although they can effectively passivate metal oxide interface defects, they have not been able to effectively modify some ionic defects at the perovskite lower interface in contact with the metal oxide interface.
[0004] The existing organic small molecule materials have relatively few functional groups that can interact with the perovskite and metal oxide interfaces, making it difficult to synergistically regulate the perovskite and metal oxide interfaces. Summary of the Invention
[0005] The technical problem to be solved by this invention is to provide a hole-modifying layer and a perovskite solar cell and a method for preparing the same. The hole-modifying layer uses a novel spirocyclic molecular functionalized material. This material can not only be bonded to the surface of the hole transport layer of the metal oxide through self-assembly, but the presence of characteristic atoms in the molecular framework structure can also synergistically passivate ionic defects at the interface of the perovskite active layer. While ensuring good interface charge extraction, it can also achieve the regulation of the perovskite crystal, thereby further improving the photoelectric conversion efficiency of the perovskite solar cell.
[0006] This invention is achieved by providing a hole-modified layer, wherein the material used to prepare the hole-modified layer is any one of N1, N2, N3, and N4, and the specific chemical structural formulas of the N1, N2, N3, and N4 materials are as follows: .
[0007] The molecular framework of the N1, N2, N3, and N4 materials includes spirocyclic framework units, which have Se and O atoms at sites that can interact with perovskite ions, and phosphate groups at the molecular ends that can bond with metal oxides.
[0008] The present invention is implemented as follows, and also provides a method for preparing the hole-modified layer as described above, comprising the following steps: selecting any one of the N1, N2, N3, and N4 materials and preparing a solution with a concentration of 0.5 mg / ml using solvent DMF; coating the solution onto the surface of the prepared hole transport layer under coating conditions of 3000 rpm rotation speed, 1000 rpm / s acceleration, and 30 s; and annealing at 100°C for 10 min to obtain the desired hole-modified layer.
[0009] This invention is implemented as follows, and also provides a perovskite solar cell, the internal structure of which includes, from bottom to top, a substrate, a transparent electrode layer, a metal oxide hole transport layer, a hole modification layer, a perovskite active layer, an electron transport layer, a hole blocking layer, and a metal electrode arranged in layers. The hole modification layer is prepared using the hole modification layer preparation method described above.
[0010] This invention is implemented as follows, and also provides a method for fabricating a perovskite solar cell, comprising the following steps: sequentially preparing a transparent conductive layer and a metal oxide hole transport layer on a cleaned substrate surface; preparing a hole modification layer on the metal oxide hole transport layer using the hole modification layer preparation method described above; and then sequentially preparing a perovskite active layer, an electron transport layer, a hole blocking layer, and a metal electrode on the surface of the hole modification layer to complete the fabrication of the perovskite solar cell.
[0011] Compared with existing technologies, the hole-modifying layer of this invention is prepared using any one of N1, N2, N3, and N4. This material not only forms an interfacial dipole on the nickel oxide surface, altering the band structure, but also allows the lone pairs of electrons on the oxygen and selenium atoms in the molecular structure of N1, N2, N3, or N4 to form bonds with lead ions in the perovskite layer, passivating buried ion defects in the perovskite. The introduction of these materials can effectively improve the performance of perovskite solar cells. Specifically, introducing N1, N2, N3, or N4 materials into perovskite solar cells can enhance the final photoelectric conversion efficiency. N1, N2, N3, or N4 materials not only effectively passivate surface defects of nickel oxide, inhibiting the degradation of perovskite by nickel oxide, and improving the carrier extraction rate at the interface while reducing carrier recombination, but also allow the oxygen atoms in their molecular structure to effectively passivate ion defects at the buried perovskite interface. By applying N1, N2, N3, or N4 materials to the pin perovskite system, the open-circuit voltage of the fabricated perovskite solar cells can be increased from 1.10V to 1.18V, and the current density can be increased from 24.42mA / cm². 2 Increased to 25.23 mA / cm 2 The photoelectric conversion efficiency increased from 22.26% to 24.73%. Attached Figure Description
[0012] Figure 1 This is a schematic diagram of the internal structure of a preferred embodiment of the perovskite solar cell of the present invention; Figure 2 This is a schematic diagram of the nuclear magnetic resonance spectrum of the N1 material prepared in Example 1 of the present invention; Figure 3 This is a schematic diagram of the process for preparing the N1 material in Example 1 of the present invention; Figure 4 This is a schematic diagram comparing the IV performance curves of the perovskite solar cells prepared in Example 2 and Comparative Example 1 of the present invention. Detailed Implementation
[0013] To make the technical problems to be solved, the technical solutions, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the present invention and are not intended to limit the present invention.
[0014] The hole-modified layer of the present invention is prepared from any one of N1, N2, N3, and N4, and the specific chemical structural formulas of the N1, N2, N3, and N4 materials are as follows: .
[0015] The preparation method of the N1 material includes the following steps: 1 molar equivalent of 10H-spiro[acridin-9,9'-selenoxanthracene], 10 ml of 1,4-dibromobutane, 0.1 molar equivalent of tetrabutylammonium bromide, and a 50% (w / w) potassium hydroxide aqueous solution are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 60°C for 12 hours. Extraction and solvent removal are performed, followed by column chromatography to obtain intermediate product I1. Intermediate product I1 and triethyl phosphite are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 160°C for 12 hours. The solvent is distilled under reduced pressure, and column chromatography is performed to obtain intermediate product I2. Intermediate product I2 is added to a dry reaction flask, followed by the addition of dioxane solvent. After purging with argon, trimethylbromosilane is added, and the mixture is reacted at room temperature for 12 hours. The solvent is removed by rotary evaporation, methanol and water are added, and the mixture is reacted at room temperature for 12 hours. Part of the solvent is removed by rotary evaporation, and the mixture is filtered to obtain the final product, N1 material.
[0016] The preparation method of the N2 material includes the following steps: 1 molar equivalent of 3',6'-dimethoxy-10H-spiro[acridin-9,9'-selenoxanthracene], 10 ml of 1,4-dibromobutane, 0.1 molar equivalent of tetrabutylammonium bromide, and 50% by mass potassium hydroxide aqueous solution are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 60°C for 12 hours. Extraction and solvent removal are performed, followed by column chromatography to obtain intermediate product I3. Intermediate product I3 and triethyl phosphite are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 160°C for 12 hours. The solvent is distilled under reduced pressure, and column chromatography is performed to obtain intermediate product I4. Intermediate product I4 is added to a dry reaction flask, followed by the addition of dioxane solvent. After purging with argon, trimethylbromosilane is added, and the mixture is reacted at room temperature for 12 hours. The solvent is removed by rotary evaporation, methanol and water are added, and the mixture is reacted at room temperature for 12 hours. Part of the solvent is removed by rotary evaporation, and the mixture is filtered to obtain the final product, N2 material.
[0017] The preparation method of the N3 material includes the following steps: 1 molar equivalent of 3',6'-bis(2-methoxyethoxy)-10H-spiro[acridin-9,9'-selenoxanthracene], 10 ml of 1,4-dibromobutane, 0.1 molar equivalent of tetrabutylammonium bromide, and 50% by mass potassium hydroxide aqueous solution are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 60°C for 12 hours. Extraction and solvent removal are performed, followed by column chromatography to obtain intermediate product I5. Intermediate product I5 and triethyl phosphite are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 160°C for 12 hours. The solvent is distilled under reduced pressure, and column chromatography is performed to obtain intermediate product I6. Intermediate product I6 is added to a dry reaction flask, followed by the addition of dioxane solvent. After purging with argon, trimethylbromosilane is added, and the mixture is reacted at room temperature for 12 hours. The solvent is removed by rotary evaporation, methanol and water are added, and the mixture is reacted at room temperature for 12 hours. Part of the solvent is removed by rotary evaporation, and the mixture is filtered to obtain the final product, N3 material.
[0018] The preparation method of the N4 material includes the following steps: 1 molar equivalent of 3',6'-bis(2-(2-methoxyethoxy)ethoxy)-10H-spiro[acridin-9,9'-selenoxanthracene], 10 ml of 1,4-dibromobutane, 0.1 molar equivalent of tetrabutylammonium bromide, and 50% by mass potassium hydroxide aqueous solution are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 60°C for 12 hours. The solvent is extracted and evaporated by rotary evaporation, and column chromatography is used to obtain intermediate product I7. Intermediate product I7 and triethyl phosphite are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 160°C for 12 hours. The solvent is distilled under reduced pressure, and column chromatography is used to obtain intermediate product I8. Intermediate product I7 is added to a dry reaction flask, followed by the addition of dioxane solvent. After purging with argon, trimethylbromosilane is added, and the mixture is reacted at room temperature for 12 hours. The solvent was evaporated, methanol and water were added, and the mixture was reacted at room temperature for 12 hours. After evaporating some of the solvent, the final product N4 material was obtained by filtration.
[0019] The present invention also discloses a method for preparing a hole-modified layer as described above, comprising the following steps: selecting any one of the N1, N2, N3, and N4 materials and preparing a solution with a concentration of 0.5 mg / ml using solvent DMF; coating the solution onto the surface of the prepared hole transport layer under coating conditions of 3000 rpm rotation speed, 1000 rpm / s acceleration, and 30 s; and annealing at 100°C for 10 min to obtain the desired hole-modified layer.
[0020] Please refer to Figure 1As shown, the present invention also discloses a perovskite solar cell, the internal structure of which includes, from bottom to top, a substrate 1, a transparent electrode layer 2, a metal oxide hole transport layer 3, a hole modification layer 4, a perovskite active layer 5, an electron transport layer 6, a hole blocking layer 7, and a metal electrode 8 arranged in layers. The hole modification layer 4 is prepared by the hole modification layer preparation method described above.
[0021] Specifically, the substrate 1 is made of glass, quartz, flexible PET, or flexible PEN; the transparent electrode layer 2 is made of indium tin oxide, fluorine-doped tin oxide, or a thin metal layer; and the metal oxide hole transport layer 3 is made of nickel oxide. The perovskite active layer 5 is made of perovskite material with the molecular formula ABX3. The A-site is a cesium ion (Cs). + ), Methylamine cation (MA) + ), formamidinium cation (FA) + At least one of the following, with the B site being a lead ion (Pb). 2+ The X position is a chloride ion (Cl). - ), bromide ions (Br) - ), iodide ions (I - At least one of the following. The electron transport layer 6 is fabricated using PCBM, C 60 Alternatively, any one of ZnO, the hole blocking layer 7 is prepared from 2,9-dimethyl-4,7-biphenyl-1,10-o-diazaphenanthroline or BCP, and the metal electrode layer 8 is prepared from any one of silver, aluminum, magnesium, copper, gold, indium tin oxide and fluorine-doped tin oxide.
[0022] The thickness of the transparent electrode layer 2 is 1~500nm, the thickness of the metal oxide hole transport layer 3 is 10~30nm, the thickness of the electron transport layer 6 is 50~100nm, the thickness of the hole blocking layer 7 is 5~10nm, and the thickness of the metal electrode layer 8 is 100~300nm.
[0023] The present invention also discloses a method for fabricating a perovskite solar cell, comprising the following steps: sequentially fabricating a transparent conductive layer and a metal oxide hole transport layer on a cleaned substrate surface; fabricating a hole modification layer on the metal oxide hole transport layer using the hole modification layer fabrication method described above; and then sequentially fabricating a perovskite active layer, an electron transport layer, a hole blocking layer, and a metal electrode on the surface of the hole modification layer to complete the fabrication of the perovskite solar cell.
[0024] Specifically, the method for fabricating the perovskite solar cell is characterized by comprising the following steps: Step 1: Using FAI, MABr, PbBr, PbI2, and CsI as raw materials, and DMF and DMSO as mixed solvents at a volume ratio of 4:1, a 1.4M solution is obtained. Then, 30 mol% MACl is added to obtain CsI. 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 3. Perovskite precursor solution, ready for use.
[0025] Step 2: Select ITO conductive glass substrate 1 and clean it sequentially for 15 min in an ultrasonic bath with detergent (2% vol, Hellmenex), deionized water, isopropanol, and ethanol, and then dry it in an air drying oven at 100℃. Add 1 mol / L ethylene glycol to a 1:1 volume ratio of nickel(II) hexahydrate and ethylenediamine, then add KCl aqueous solution at a 5% molar ratio, stir at room temperature, and filter through an organic filter with a 22-micron pore size to obtain a nickel oxide precursor solution. First, treat the surface of ITO conductive layer 2 with ultraviolet-ozone for 20 min, then drop the nickel oxide precursor solution onto the treated surface of ITO conductive layer 2, spin-coat at 4000 rpm for 60 s, pre-treat at 120℃ for 10-15 min, then anneal at 300℃ for 1 h, remove at 150℃, and store in a nitrogen glove box to obtain nickel oxide metal oxide hole transport layer 3.
[0026] Step 3: Prepare hole modification layer 4 in metal oxide hole transport layer 3 using the hole modification layer preparation method described above.
[0027] Step 4: Rapidly add 60 μL of perovskite precursor solution onto the hole-modified layer 4. Spin coat at 4000 rpm for 40 seconds. Add 120 μL of isopropanol 30 seconds after spin coat begins. After spin coat stops, anneal the resulting perovskite wet film on a 100°C hot plate for 30 minutes. After cooling, spin coat an organic ammonium salt solution (isopropanol, 2 mg / mL) at 5000 rpm. Anneal the perovskite wet film again on a 100°C hot plate for 5 minutes. After cooling, the perovskite active layer 5 is obtained. Spin coat PCBM and BCP onto the surface of the perovskite active layer 5 at 3000 rpm. PCBM is chlorobenzene (20 mg / mL), and BCP is ethanol (0.5 mg / mL). The PCBM film is the electron transport layer 6, and the BCP film is the hole-blocking layer 7. Finally, Ag was deposited on the BCP thin film layer using a vapor deposition apparatus to obtain metal electrode 8, thus obtaining the desired Cs. 0.05 (FA 0.95 MA 0.05 )0.95 Pb(I 0.95 Br 0.05 )3 is a perovskite solar cell with a perovskite active layer.
[0028] The following specific embodiments further illustrate a hole-modifying layer and a perovskite solar cell of the present invention and their preparation method.
[0029] Example 1
[0030] The first embodiment of the method for preparing the N1 material in the hole-modifying layer of the present invention includes the following steps: Step 11: Under argon protection, 500.0 mg of 10H-spiro[acridin-9,9'-selenoxanthracene], 10 mL of 1,4-dibromobutane, 160.0 mg of 0.50 mmol of tetrabutylammonium bromide, and 2.5 mL of 50% KOH aqueous solution were placed in a dry reaction tube. The argon gas was purged, and the mixture was heated to reflux at 60 °C for 12 h. After the reaction was complete, the reaction solution was extracted with dichloromethane, the organic phase was collected, the organic solvent was removed by rotary evaporation, and the crude product was purified by silica gel chromatography to obtain 457.0 mg of intermediate I1. Intermediate I1 was a white product with a yield of 69%.
[0031] Step 12: Under argon protection, 450.0 mg and 0.83 mmol of intermediate product I1 and 10 mL of triethyl phosphite were placed in a dry reaction tube, the argon gas was replaced, and the mixture was heated to reflux at 160 °C for 12 h. After the reaction was completed, the solvent was removed by vacuum distillation, and the crude product was purified by silica gel chromatography to obtain 400.0 mg of intermediate product I2, which was a white oily product with a yield of 80%.
[0032] Step 13: Under argon protection, 400.0 mg and 0.66 mmol of intermediate product I2 and 10 ml of dioxane were placed in a dry reaction tube. The argon gas was replaced, and 1016.2 mg and 6.64 mmol of trimethylbromosilane were added. The mixture was stirred at room temperature for 12 h. Then, the solvent was removed by rotary evaporation, and 10 ml of methanol and 1 ml of deionized water were added. The mixture was stirred at room temperature for 12 h, and some of the solvent was removed by rotary evaporation. A solid precipitated and was filtered to obtain 300 mg of the final product N1 material. N1 material was a white solid with a yield of 83%.
[0033] The N1 material prepared in this embodiment was subjected to NMR analysis, and the results were as follows: Figure 2 The NMR spectrum shown is shown in the figure. As can be seen from the figure... 1HNMR(400MHZ, DMSO-d6)δ:7.31-7.13(m,8H),7.00-6.92(m,2H),6.88-6.85(m,2H), 6.74-6.67(m,2H),6.64-6.59(m,2H),4.08-4.00(m,2H),1.88(s,2H),2.03(s,6H),1.76-1.66(m,4H).
[0034] The above reaction process is as follows Figure 3 As shown.
[0035] Example 2
[0036] The first embodiment of the method for preparing perovskite solar cells of the present invention includes the following steps: Step 21: Using FAI, MABr, PbBr, PbI2, and CsI as raw materials, and DMF and DMSO as mixed solvents at a volume ratio of 4:1, a 1.4 M solution is obtained. Then, 30 mol% MACl is added to obtain CsI. 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 3. Perovskite precursor solution, ready for use.
[0037] Step 22: Select ITO conductive glass substrate 1 and clean it sequentially for 15 min in an ultrasonic bath with detergent (2% vol, Hellmenex), deionized water, isopropanol, and ethanol, and then dry it in an air drying oven at 100℃. Add 1 mol / L ethylene glycol to a 1:1 volume ratio of nickel(II) hexahydrate and ethylenediamine, then add KCl aqueous solution at a 5% molar ratio, stir at room temperature, and filter through an organic filter with a 22-micron pore size to obtain a nickel oxide precursor solution. First, treat the surface of ITO conductive layer 2 with ultraviolet-ozone for 20 min, then drop the nickel oxide precursor solution onto the treated surface of ITO conductive layer 2, spin-coat at 4000 rpm for 60 s, pre-treat at 120℃ for 10-15 min, then anneal at 300℃ for 1 h, remove at 150℃, and store in a nitrogen glove box to obtain nickel oxide metal oxide hole transport layer 3.
[0038] Step 23: Select the N1 material and solvent DMF to prepare a solution with a concentration of 0.5 mg / ml. Apply the solution to the surface of the prepared hole transport layer at a coating speed of 3000 rpm, an acceleration of 1000 rpm / s, and a coating time of 30 s. Anneal at 100°C for 10 min to obtain the desired hole-modified layer.
[0039] Step 24: Rapidly add 60 μL of perovskite precursor solution onto the hole-modified layer 4. Spin coat at 4000 rpm for 40 s. Add 120 μL of isopropanol 30 s after spin coat begins. After spin coat stops, anneal the resulting perovskite wet film on a 100°C hot plate for 30 min. After cooling, spin coat an organic ammonium salt solution (isopropanol, 2 mg / mL) at 5000 rpm. Anneal the perovskite wet film again on a 100°C hot plate for 5 min. After cooling, the perovskite active layer 5 is obtained. Spin coat PCBM and BCP onto the surface of the perovskite active layer 5 at 3000 rpm. PCBM is chlorobenzene (20 mg / mL), and BCP is ethanol (0.5 mg / mL). The PCBM film is the electron transport layer 6, and the BCP film is the hole-blocking layer 7. Finally, Ag was deposited on the BCP thin film layer using a vapor deposition apparatus to obtain metal electrode 8, thus obtaining the desired Cs. 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3 is a perovskite solar cell with a perovskite active layer.
[0040] Example 3
[0041] The second embodiment of the method for preparing perovskite solar cells of the present invention differs from embodiment 2 in that: in step 23, N2 material is used instead of N1 material. Other steps and conditions are the same as in embodiment 2 and will not be repeated here.
[0042] Example 4
[0043] The third embodiment of the method for preparing perovskite solar cells of the present invention differs from embodiment 2 in that: in step 23, N3 material is selected to replace N1 material. Other steps and conditions are the same as in embodiment 2 and will not be repeated.
[0044] Example 5
[0045] The fourth embodiment of the method for preparing perovskite solar cells of the present invention differs from embodiment 2 in that: in step 23, N4 material is used instead of N1 material. The other steps and conditions are the same as in embodiment 2 and will not be repeated here.
[0046] Comparative Example 1 The first comparative example of the method for preparing perovskite solar cells of the present invention includes the following steps: Step D1: Using FAI, MABr, PbBr, PbI2, and CsI as raw materials, and DMF and DMSO as mixed solvents at a volume ratio of 4:1, a 1.4 M solution is obtained. Then, 30 mol% MACl is added to obtain CsI. 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 3. Perovskite precursor solution, ready for use.
[0047] Step D2: Select ITO conductive glass substrate 1 and clean it sequentially for 15 min in an ultrasonic bath of detergent (2% vol, Hellmenex), deionized water, isopropanol, and ethanol, and then dry it in an air drying oven at 100℃. Add 1 mol / L ethylene glycol to a 1:1 volume ratio of nickel(II) hexahydrate and ethylenediamine, then add KCl aqueous solution at a 5% molar ratio, stir at room temperature, and filter through an organic filter with a 22-micron pore size to obtain a nickel oxide precursor solution. First, treat the surface of ITO conductive layer 2 with ultraviolet-ozone for 20 min, then drop the nickel oxide precursor solution onto the treated surface of ITO conductive layer 2, spin-coat at 4000 rpm for 60 s, pre-treat at 120℃ for 10-15 min, then anneal at 300℃ for 1 h, remove at 150℃, and store in a nitrogen glove box to obtain nickel oxide metal oxide hole transport layer 3.
[0048] Step D4: Rapidly add 60 μL of perovskite precursor solution onto hole transport layer 3. Spin coat at 4000 rpm for 40 s. Add 120 μL of isopropanol 30 s after spin coat begins. After spin coat stops, anneal the resulting perovskite wet film on a 100°C hot plate for 30 min. After cooling, spin coat an organic ammonium salt solution (isopropanol, 2 mg / mL) at 5000 rpm. Anneal the perovskite wet film again on a 100°C hot plate for 5 min. After cooling, the perovskite active layer 5 is obtained. Spin coat PCBM and BCP onto the surface of perovskite active layer 5 at 3000 rpm. PCBM is chlorobenzene (20 mg / mL), and BCP is ethanol (0.5 mg / mL). The PCBM film is the electron transport layer 6, and the BCP film is the hole blocking layer 7. Finally, Ag was deposited on the BCP thin film layer using a vapor deposition apparatus to obtain metal electrode 8, thus obtaining the desired Cs. 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3 is a perovskite solar cell with a perovskite active layer.
[0049] The perovskite solar cells prepared in Example 2 and Comparative Example 1 were subjected to IV performance tests, and the results were obtained. Figure 4 The diagram shows a comparison of IV performance curves, and Table 1 shows a comparison of performance test data.
[0050] During IV performance testing, the light intensity was 100 mW / cm². 2 The perovskite solar cell sample to be tested was subjected to AM 1.5G simulated sunlight irradiation.
[0051] Table 1. Comparison of performance test data of perovskite solar cells prepared in Example 2 and Comparative Example 1
[0052] from Figure 4 As shown in Table 1, the open-circuit voltage of the perovskite solar cell in Comparative Example 1 (i.e., without N1 material modification on nickel oxide) is 1.10V, and the short-circuit current density is 24.42mA / cm². 2 The fill factor is 83.86, and the photoelectric power conversion efficiency is 22.26%. The open-circuit voltage of the perovskite solar cell in Example 2, based on the N1 material modification layer, is 1.18V, and the short-circuit current density is 25.23mA / cm². 2 The fill factor is 83.10, and the photoelectric energy conversion efficiency is 24.73%. The photoelectric energy conversion efficiency is higher than that of Comparative Example 1.
[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A hole-modified layer, characterized in that, The hole-modified layer is prepared from any one of N1, N2, N3, and N4, and the specific chemical structural formulas of N1, N2, N3, and N4 are as follows: 。 2. The hole-modifying layer as described in claim 1, characterized in that, The preparation method of the N1 material includes the following steps: 1 molar equivalent of 10H-spiro[acridin-9,9'-selenoxanthracene], 10 ml of 1,4-dibromobutane, 0.1 molar equivalent of tetrabutylammonium bromide, and 50% by mass of potassium hydroxide aqueous solution are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 60°C for 12 hours. The solvent is extracted and evaporated by rotary evaporation, and the intermediate product I1 is obtained by column chromatography. Intermediate product I1 and triethyl phosphite are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 160°C for 12 hours. The solvent is distilled under reduced pressure, and the intermediate product I2 is obtained by column chromatography. Intermediate product I2 is added to a dry reaction flask, and then dioxane is added as solvent. After purging with argon, trimethylbromosilane is added, and the mixture is reacted at room temperature for 12 hours. The solvent is evaporated by rotary evaporation, methanol and water are added, and the mixture is reacted at room temperature for 12 hours. Part of the solvent is removed by rotary evaporation, and the mixture is filtered to obtain the final product N1 material.
3. The hole-modifying layer as described in claim 1, characterized in that, The preparation method of the N2 material includes the following steps: 1 molar equivalent of 3',6'-dimethoxy-10H-spiro[acridin-9,9'-selenoxanthracene], 10 ml of 1,4-dibromobutane, 0.1 molar equivalent of tetrabutylammonium bromide, and 50% by mass of potassium hydroxide aqueous solution are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 60°C for 12 hours. The solvent is extracted and evaporated by rotary evaporation, and column chromatography is used to obtain intermediate product I3. Intermediate product I3 and triethyl phosphite are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 160°C for 12 hours. The solvent is distilled under reduced pressure, and column chromatography is used to obtain intermediate product I4. Intermediate product I4 is added to a dry reaction flask, and then dioxane is added as solvent. After purging with argon, trimethylbromosilane is added, and the mixture is reacted at room temperature for 12 hours. The solvent is evaporated by rotary evaporation, methanol and water are added, and the mixture is reacted at room temperature for 12 hours. Part of the solvent is removed by rotary evaporation, and the mixture is filtered to obtain the final product N2 material.
4. The hole-modifying layer as described in claim 1, characterized in that, The preparation method of the N3 material includes the following steps: 1 molar equivalent of 3',6'-bis(2-methoxyethoxy)-10H-spiro[acridin-9,9'-selenoxane], 10 ml of 1,4-dibromobutane, 0.1 molar equivalent of tetrabutylammonium bromide, and 50% by mass of potassium hydroxide aqueous solution are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 60°C for 12 hours. The solvent is extracted and evaporated by rotary evaporation, and column chromatography is used to obtain intermediate product I5. Intermediate product I5 and triethyl phosphite are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 160°C for 12 hours. The solvent is distilled under reduced pressure, and column chromatography is used to obtain intermediate product I6. Intermediate product I6 is added to a dry reaction flask, followed by the addition of dioxane solvent. After purging with argon, trimethylbromosilane is added, and the mixture is reacted at room temperature for 12 hours. The solvent is evaporated by rotary evaporation, methanol and water are added, and the mixture is reacted at room temperature for 12 hours. Part of the solvent is removed by rotary evaporation, and the mixture is filtered to obtain the final product N3 material.
5. The hole-modifying layer as described in claim 1, characterized in that, The preparation method of the N4 material includes the following steps: 1 molar equivalent of 3',6'-bis(2-(2-methoxyethoxy)ethoxy)-10H-spiro[acidine-9,9'-selenoxane], 10 ml of 1,4-dibromobutane, 0.1 molar equivalent of tetrabutylammonium bromide, and a 50% (w / w) potassium hydroxide aqueous solution are added to a dry reaction flask. After purging with argon, the mixture is heated to reflux at 60°C for 12 hours. The mixture is then extracted, the solvent is evaporated, and column chromatography is used to obtain the intermediate product. Intermediate I7; intermediate I7 and triethyl phosphite were added to a dry reaction flask, purged with argon, and heated to reflux at 160°C for 12 hours. The solvent was then distilled under reduced pressure, and column chromatography was used to obtain intermediate I8. Intermediate I7 was added to a dry reaction flask, followed by the addition of dioxane solvent. After purging with argon, trimethylbromosilane was added, and the reaction was carried out at room temperature for 12 hours. The solvent was evaporated, methanol and water were added, and the reaction was carried out at room temperature for 12 hours. Part of the solvent was evaporated, and the mixture was filtered to obtain the final product N4 material.
6. A method for preparing a hole-modified layer as described in any one of claims 1 to 5, characterized in that, The process includes the following steps: selecting any one of the N1, N2, N3, and N4 materials and preparing a solution with a concentration of 0.5 mg / ml using the solvent DMF; coating the solution onto the surface of the prepared hole transport layer under coating conditions of 3000 rpm rotation speed, 1000 rpm / s acceleration, and 30 s; and annealing at 100°C for 10 min to obtain the desired hole-modified layer.
7. A perovskite solar cell, characterized in that, Its internal structure includes a substrate (1), a transparent electrode layer (2), a metal oxide hole transport layer (3), a hole modification layer (4), a perovskite active layer (5), an electron transport layer (6), a hole blocking layer (7), and a metal electrode (8) arranged in layers from bottom to top, wherein the hole modification layer (4) is prepared by the hole modification layer preparation method described in claim 6.
8. The perovskite solar cell according to claim 7, characterized in that, The substrate (1) is made of glass, quartz, flexible PET, or flexible PEN; the transparent electrode layer (2) is made of indium tin oxide, fluorine-doped tin oxide, or a thin metal layer; the metal oxide hole transport layer (3) is made of nickel oxide; the perovskite active layer (5) is made of perovskite material with the molecular formula ABX3, wherein the A site is a cesium ion (Cs). + ), Methylamine cation (MA) + ), formamidinium cation (FA) + At least one of the following, with the B site being a lead ion (Pb). 2+ The X position is a chloride ion (Cl). - ), bromide ions (Br) - ), iodide ions (I - At least one of the following: the electron transport layer (6) is made of PCBM, C 60 Alternatively, any one of ZnO, the hole blocking layer (7) is prepared by 2,9-dimethyl-4,7-biphenyl-1,10-o-diazaphenanthroline or BCP, the metal electrode layer (8) is prepared by any one of silver, aluminum, magnesium, copper, gold, indium tin oxide and fluorine-doped tin oxide, wherein the thickness of the transparent electrode layer (2) is 1~500nm, the thickness of the metal oxide hole transport layer (3) is 10~30nm, the thickness of the electron transport layer (6) is 50~100nm, the thickness of the hole blocking layer (7) is 5~10nm, and the thickness of the metal electrode layer (8) is 100~300nm.
9. A method for fabricating a perovskite solar cell, characterized in that, The process includes the following steps: a transparent conductive layer (2) and a metal oxide hole transport layer (3) are sequentially prepared on the surface of a cleaned substrate (1). A hole modification layer (4) is prepared on the metal oxide hole transport layer (3) using the hole modification layer preparation method described in claim 6. Then, a perovskite active layer (5), an electron transport layer (6), a hole blocking layer (7), and a metal electrode (8) are sequentially prepared on the surface of the hole modification layer (4) to complete the preparation of the perovskite solar cell.
10. The method for preparing a perovskite solar cell as described in claim 9, characterized in that, Includes the following steps: Step 1: Using FAI, MABr, PbBr, PbI2, and CsI as raw materials, and DMF and DMSO as mixed solvents at a volume ratio of 4:1, a 1.4M solution is obtained. Then, 30 mol% MACl is added to obtain CsI. 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 3) Perovskite precursor solution, ready for use; Step 2: Select an ITO conductive glass substrate (1) and clean it sequentially in an ultrasonic bath of detergent, deionized water, isopropanol and ethanol for 15 min, and then dry it in an air drying oven at 100℃; add 1 mol / L ethylene glycol to nickel(II) hexahydrate and ethylenediamine in a volume ratio of 1:1, and then add KCl aqueous solution at a molar ratio of 5%, and stir at room temperature. Filter the solution with an organic filter head with a pore size of 22 micrometers to obtain a nickel oxide precursor solution; first treat the surface of the ITO conductive layer (2) with ultraviolet-ozone for 20 min, then drop the nickel oxide precursor solution onto the treated surface of the ITO conductive layer (2), spin coat it at a speed of 4000 rpm for 60 s, pretreat it at 120℃ for 10~15 min, and then anneal it on a hot table at 300℃ for 1 h, remove it at 150℃, and store it in a nitrogen glove box to obtain a nickel oxide metal oxide hole transport layer (3). Step 3: Prepare a hole-modifying layer (4) in the metal oxide hole transport layer (3) using the hole-modifying layer preparation method as described in claim 6. Step 4: Rapidly add 60 μL of perovskite precursor solution onto the hole-modified layer (4). Set the spin coating speed to 4000 rpm for 40 s. Add 120 μL of isopropanol 30 s after the spin coating starts. After the spin coating stops, place the obtained perovskite wet film on a hot plate at 100°C for annealing for 30 min. After cooling, spin coat the organic ammonium salt solution at 5000 rpm. The solvent of the organic ammonium salt solution is isopropanol with a concentration of 2 mg / mL. Then place the perovskite wet film on a hot plate at 100°C for annealing. After heating for 5 minutes and cooling, a perovskite active layer (5) was obtained. PCBM and BCP were spin-coated onto the surface of the perovskite active layer (5) at 3000 rpm. The solvent for PCBM was chlorobenzene with a concentration of 20 mg / mL, and the solvent for BCP was ethanol with a concentration of 0.5 mg / mL. The PCBM film layer served as an electron transport layer (6), and the BCP film served as a hole blocking layer (7). Finally, Ag was deposited onto the BCP film layer using a vapor deposition apparatus to obtain a metal electrode (8), yielding the desired Cs-based electrode. 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3 is a perovskite solar cell with a perovskite active layer.
